Digital economy integration in Asia and the Pacific: Insights from DigiSRII 1.0 - Witada Anukoonwattaka; Pedro Romao; Preety Bhogal; Thomas Bentze; Richard S. Lobo (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2021)
In this paper, we utilize ESCAP (2020)'s framework of Digital and Sustainable Regional Integration Index version 1 (DigiSRII 1.0) to uncover digital economy integration trends across Asia-Pacific region. The results show that Asia and the Pacific has progressed well on conventional digital economy integration, especially due to significant improvements on digital-economy infrastructure and ICT goods trade liberalization. However, workforce capacitation and infrastructures investments are essential to bridge digitalization gaps between digitalized economies in the region. Moreover, the fairly low regulatory similarity between regional economies further highlights the importance of regional regulatory harmonization in order to foster regional trade in digitally-enabled goods and services. From a sustainable development perspective, inclusivity and equity of access to digitalization and required infrastructure remain key challenges. It is found that while internet penetration in the region has been getting higher, female participation in digital economy is relatively low in general and extremely low in low-income economies. In addition, there is room to enhance cybersecurity in most of Asia-Pacific economies. Regional digital policies should focus on harmonizing data protection protocols and building a safer network of servers that can promote economic activity and sensitive matters to be conducted online. Fostering a more inclusive digital transformation may considerably boost network-effects and accelerate the transition to a competitive and sustainable regional digital economy.
Keywords: F15; O24; O53; 330; international trade; regional integration; digitalization; digital economy